2014
DOI: 10.3389/fimmu.2014.00391
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to HIV in Early Life

Abstract: The developing immune system is adapted to the exposure to a plethora of pathogenic and non-pathogenic antigens encountered in utero and after birth, requiring a fine balance between protective immunity and immune tolerance. In early stages of life, this tolerogenic state of the innate and adaptive immune system and the lack of immunological memory render the host more susceptible to infectious pathogens like HIV. HIV pathogenesis is different in children, compared to adults, with more rapid disease progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 203 publications
(252 reference statements)
1
78
0
3
Order By: Relevance
“…The dynamics of HIV persistence in children are probably different than those in adults, owing to a number of factors such as the types and numbers of target cells, efficiency in clearing HIV-infected cells, and pharmacokinetics of ART in blood and tissues. Little is known about the development of the newborn and infant innate and adaptive immune system, and about the role of immune activation, homeostasis, inflammation, and viral and host factors in the establishment and maintenance of HIV latency 70 . Early ART can preserve normal development of B and T cells, as demonstrated by the ability to mount immune responses against childhood vaccines.…”
Section: Hiv Remission In the Pediatric Populationmentioning
confidence: 99%
“…The dynamics of HIV persistence in children are probably different than those in adults, owing to a number of factors such as the types and numbers of target cells, efficiency in clearing HIV-infected cells, and pharmacokinetics of ART in blood and tissues. Little is known about the development of the newborn and infant innate and adaptive immune system, and about the role of immune activation, homeostasis, inflammation, and viral and host factors in the establishment and maintenance of HIV latency 70 . Early ART can preserve normal development of B and T cells, as demonstrated by the ability to mount immune responses against childhood vaccines.…”
Section: Hiv Remission In the Pediatric Populationmentioning
confidence: 99%
“…This Th2-directed bias in early life is likely to be an adaptation that has evolved to prevent harmful pro-inflammatory Th1 responses against maternal allo-antigens while in-utero (8) and the plethora of newly encountered environmental antigens after birth (3). However, this ‘approach’ compromises immunity to intracellular pathogens such as HIV (9). …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have claimed that infants may have impaired immune responses to HIV infection compared to adults (40). However, we previously demonstrated that vaccination of infants can induce robust HIV Env-specific IgG responses (41).…”
Section: Discussionmentioning
confidence: 99%